Past local government health spending was not correlated with COVID-19 control in US counties - Sneha Lamba; Carrie Wolfson; Carolina Cardona; Y. Natalia Alfonso; Alison Gemmill; Beth Resnick; Jonathon P. Leider; J. Mac McCullough; David Bishai (Elsevier, 2022)
Context: Wide variation in state and county health spending prior to 2020 enables tests of whether historically better state and locally funded counties achieved faster control over COVID-19 in the first 6 months of the pandemic in the Unites States prior to federal supplemental funding. Objective: We used time-to-event and generalized linear models to examine the association between pre-pandemic state-level public health spending, county-level non-hospital health spending, and effective COVID-19 control at the county level. We include 2,775 counties that reported 10 or more COVID-19 cases between January 22, 2020, and July 19, 2020, in the analysis. Main outcome measure: Control of COVID-19 was defined by: (i) elapsed time in days between the 10th case and the day of peak incidence of a county's local epidemic, among counties that bent their case curves, and (ii) doubling time of case counts within the first 30 days of a county's local epidemic for all counties that reported 10 or more cases. Results: Only 26% of eligible counties had bent their case curve in the first 6 months of the pandemic. Government health spending at the county level was not associated with better COVID-19 control in terms of either a shorter time to peak in survival analyses, or doubling time in generalized linear models. State-level public spending on hazard preparation and response was associated with a shorter time to peak among counties that were able to bend their case incidence curves. Conclusions: Increasing resource availability for public health in local jurisdictions without thoughtful attention to bolstering the foundational capabilities inside health departments is unlikely to be sufficient to prepare the country for future outbreaks or other public health emergencies.